Co-firing of coal/biomass blends in a pilot plant facility: A comparative study between Opuntia ficus-indica and Pinus radiata. (15th February 2018) - Pérez-Jeldres, Rubén; Flores, Mauricio; Cornejo, Pablo; Gordon, Alfredo; García, Ximena
Abstract: Chile has begun to promote the use of biomass to replace a fraction of the energy produced from coal. However, the power plants are located in the world driest desert, the Atacama Desert, and far from the forest resources. Fortunately, a cactaceous species named Opuntia ficus-indica, has proven to be able to grow under climate desert conditions. In this study the behavior of Opuntia ficus-indica under co-firing conditions with coal, is evaluated and compared to that of Pinus radiata, in terms of heat transfer, ash deposits formation and pollutant emissions in a 150 kW fluidized bed pilot plant. The results revealed a variation of the temperature profile inside the reactor, as well as a relationship between the efficacy factor and the base-acid ratio. The heat transfer coefficients in the dense bed evidenced a decrease in the heat transfers mechanisms attributed to a variation of the mean particle diameter and a greater presence of fuel particles. Under coal-Pine co-firing conditions, an increase in NO formation and a decrease of PM and SO2 concentrations was observed. While co-firing coal with Opuntia showed an increase in the particulate matter and a reduction of NO and SO2 concentrations. Highlights: Opuntia (Cactaceae), which grows well in deserts was assayed in biomass-coal firing. Heat transfer in a fluidized bed for co-firing is affected by the type of biomass. Well known correlations for coal combustion were tried for biomass-coal firing. Moderate content of Pine does not affect steam generation by co-firing. Pine and Opuntia show differences in the emission of particles and pollutant gases.